Development of the hotel industry based on the use of information technologies - M. A. Zhukova (Управление)
The author considers in the article the main trends that will be characteristic of the entire hospitality industry in the coming years: the use of mobile payments, the changing priorities of the modern consumer, the environmentally friendly thinking of the consumer, the individualization of services in hotels, the presence of chat bots, the creation of «smart» and wellness rooms with using voice activation and Internet commands, installation in hotels of digital kiosks, self check-in and check-out of a guest using information technologies, digital equipment polar fund hotels, use of a mobile phone as a lock to the number, availability in the hotels of interactive social networking innovations, the use of SMS-notifications in the loyalty program, the active use of internet marketing. Examples of hotels that are already actively introducing modern innovations into business practice, have provided. The importance of individualization of services in accommodation facilities has shown by the example of researching the experience of international hotel chains. The experience of hotel chains on the formation of levels of consumer loyalty programs, as well as the conditions for obtaining and privileges of Marriott Rewards card holders have examined. The basic principles that the hotel must adhere to in order to retain the consumer and ensure his repeated visits to the hotel have identified: addressing each guest by name; collect contact information from guests and e-mail; encouraging guests to write reviews; studying the preferences and requirements of guests; providing quality service; preferably direct booking. Recommendations for hotel management to create programs to increase consumer loyalty have developed, as well as a set of technical innovations, the introduction of which hotels in the near future need to pay special attention has formed.